Nitrogen fertilizer replacement indexes of legume cover crops in the derived savanna of West Africa - Tian, G.; Kolawole, G.O.; Kang, B.T.; Kirchhof, G. (2000)
Legume cover crops are a potential means for overcoming N depletion in the derived savanna of West Africa. A 3-year trial was, therefore, conducted near Ibadan, southwestern Nigeria to measure the N contribution of 13 legume cover crops as compared to urea –N, using a N fertilizer replacement index for a maize test crop. Two series of trials involved the following legume cover crop species: Aeschynomene histrix, Centrosema brasilianum, Centrosema pascuorum, Chamaecrista rotundifolia, Cajanus cajan, Crotalaria verrucosa, Crotalaria ochroleuca, Lablab purpureus, Mucuna pruriens, Psophocarpus palustris, Pseudovigna argentea, Pueraria phaseoloides and Stylosanthes hamata. Trials were undertaken using a complete block design. Cover crops were planted in 1994 (Series 1) and 1995 (Series 2) in separate sites and each series was subsequently slashed and planted for one season with maize (Zea mays) in 1995 and 1996. At the 50% flowering stage, N concentration of above-ground vegetation of cover crops ranged from 21 to 38 g N kg−1. Nitrogen accumulated by 4.5-month old cover crops ranged from 14 to 240 kg N ha−1, depending on species and year. Cover crops increased grain yield of the subsequent maize crop by 25–136% over the control without N application. Nitrogen uptake by the maize crop was higher following cover crops than after maize or natural grass. The N fertilizer replacement index of cover crops for maize ranged from 11 (A. histrix) to 96 kg N ha−1 (C. cajan) in Series 2. Perennial (C. brasilianum, S. hamata, C. cajan, P. phaseoloides and C. verrucosa) and annual (C. rotundifolia, M. pruriens, C. ochroleuca and L. purpureus) species could potentially save 50 to 100 kg N ha−1 for maize crops. The cover crops accumulated more N in the wetter than in the drier year. However, the N fertilizer replacement index was higher for subsequent maize grown in the drier year. The cover crop-N recovery in maize was also higher than the urea-N uptake in the drier year. The N fertilizer replacement indexes can be predicted using the above-ground biomass amount of cover crops at 20 weeks after planting (drier year) or the N concentration at that stage (wetter year).